Pemanfaatan Augmented Reality dalam Pembelajaran IPS Menyajikan Informasi Sejarah dengan Realitas Tambahan - Nabila Putri Wahiddiyah; Ayudhia Nur Luthfia; Desy Safitri; Sujarwo Sujarwo (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Utilization of Augmented Reality (AR) in learning Social Sciences (IPS) with a focus on presenting historical information. Augmented Reality is a technology that allows users to see the real world with the addition of digital elements, such as images, text, or 3D objects inserted in the physical environment. This research illustrates how AR can be used in social studies learning to improve students' understanding of history. By integrating AR into the learning experience, students can access additional information visually and interactively. For example, they can "see" historical figures or historical events through 3D projections that appear on top of textbooks or other learning materials. The results of this research show that the use of AR in social studies learning can increase student engagement, increase their understanding of historical material, and make learning more interesting. Apart from that, the use of AR also allows personalized learning and is tailored to students' abilities and interests. Thus, the use of AR in social studies learning, especially in the context of presenting historical information, can be an effective tool for creating a deeper and more interesting learning experience for students. Further research and development of more sophisticated AR applications in this area could be the next step in utilizing this technology in education.